Термогенез у рослин - Посудін, Ю.І. (Енергетика і автоматика, 2017)
UDC 535.37THERMOGENESIS IN PLANTSYuriy Posudin             Thermogenesis is the process of heat production in plants that allows them to maintain own temperature higher than the ambient temperature.         Currently, there are several theories to explain the phenomenon of thermogenesis in plants. One of them is based on the assumption that the plant heat is responsible for distributing chemicals and relevant attracting insect pollinators to flowers. In this case, the heat helps to spread the aroma (for example, of rotten meat) and to attract insects.         Another theory states that heat helps to protect plants from cold temperatures. In this case thermogenic plants should sprout earlier than conventional plants.         Thermogenesis by flowers occurs in several families of plants, including Araceae, Arecaceae, Aristolochiaceae, Annonaceae, Cycadaceae, Cyclanthaceae, Magnoliaceae, Nelumbonaceae and Nymphaeaceae [Seymour & Schultze-Motel 1997].       There are two principal mechanisms by which mitochondrial electron transport can be uncoupled from ATP regeneration. The first one involves the alternative oxidase (AOX), which occurs in all plants [McIntosh, 1994].         The second mechanism is based on the uncoupling proteins (UCP) [Vercesi et al., 1995].         A striking example of thermogenic plants is skunk cabbage (Symplocarpus foetidus Salisb.), which grows on the eastern coast of theUnited States. This plant is distinguished by the ability to maintain the temperature in the range of 3,5 ° C only (22.7-26.2 ° C) above the ambient temperatures that varies from ‒10.3 to +27,1 ° C [Seymour 2004] in order to melt the surrounding snow early spring.Keywords: thermogenesis, plants, principal hypothesis